Clue Krewe : a Miss Fortune mystery - DeLeon, Jana (DeLeon, Jana. Miss Fortune mystery, 2023)
Beckett Rousseau is the firstborn son of one of New Orleans' most prominent families. He's the quintessential golden boy--great looks, money, and a political career in his future--until his wife murders him. Or at least that's what everyone thinks. Athena Durand is still reeling from her murder conviction but now that it's overturned, she's at a loss on how to proceed with her life. As long as people still believe she's guilty, she has no future in Louisiana and more importantly, she wants to know who killed her husband. When she hears about Fortune's exploits, Athena knows she is the one person who might be able to give her answers, and her life back. But too many people are harboring secrets about Beckett's life and death, including Athena. Can Fortune sort through the half-truths and lies to discover the truth? Or did the jury get it right the first time?